Does GDP Affect Tax Revenue? - Juliannisa, Indri Arrafi; Parianom, Raden; Abrianto, Andi (Economics Department, Faculty of Economic and Islamic Business, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
Indonesia's largest revenue comes from taxes which function to fund expenses. The increase in tax revenues must be in line with Indonesia's economic growth which is reflected in the Gross Domestic Product (GDP). This study analyzes the effect of GDP revenue on total tax revenue in Indonesia during 1988-2021 using control variables including; the money supply (M2), the population (POP), and the amount of exports and imports (XM). GRDP is the main variable because it has 17th sectors which an important in supporting economic growth and increasing the burden of tax objects. This study used a quantitative descriptive method with the Newey-West HAC method. The results showed that this study was unbiased, GDP had a positive-significant effect as indicated by the percentage of GDP growth with an average of 7% during the study period. The control variables that have a positive-significant effect are M2 and XM, and the population is not significant because the increase in the population does not support awareness of paying taxes. When there is an increase in GDP, it can provide an increase in tax revenue, as well as if there is an increase in the money supply (M2) and exports-imports (XM). Increasing revenue in GDP, M2 and XM can support the creation of new revenue objects for taxes, this is what will support the development process, especially in terms of financing. In order to increase financing for the development process, the government continues to seek sources of tax objects, not only from sectors in GDP, but also from potential export-import, and all transactions that can increase the money supply.